Metz’s Semiotic Analysis of Social Collectivism in The Animated Film Jumbo - Atsarina Luthfiyyah; Margaretha Evi Yuliana; Alfin Yoga Kharisma; Rahmaditya Khadifa Abdul Rozzaq Wijaya (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2026)
This research aims to analyze the representation of social collectivity in the animated film Jumbo using Christian Metz’s semiotic approach. The method employed is descriptive-interpretive, with data collection techniques including visual observation and screen captures of animated film scenes. The results indicate that social collectivity is constructed through cinematic signs such as interactions in public spaces, shared activities, and cooperation among characters. The narrative structure illustrates a progression from isolation toward social integration through conflict and reconciliation. Collectivity is not merely present as an explicit message but also as a construction of meaning formed through the relationships between scenes, characters, and social spaces, thereby reinforcing the values of togetherness, solidarity, and mutual aid.